Pemberdayaan Kompetensi Mahasiswa Akhir Program Studi Pendidikan Dokter dalam Melakukan Promosi Kesehatan Olahraga - Arwan Bin Laeto; Budi Santoso; Eka Febri Zulissetiana; Susilawati Susilawati (Muria Jurnal Layanan Masyarakat, 2023)
Athis community service activity aims to empower the competence of final semester students of the Medical Education Study Program, Faculty of Medicine, Sriwijaya University, in implementing the concepts and knowledge they already have through organizing sports health promotion activities. The novelty of this activity is that early students are trained to develop effective communication competencies with the general public before actually being in the community, according to profession they occupy. The result of this community service is that students become skilled in promoting sports health as a result of empowering the knowledge and insights that have been obtained in the early semester.